Protein Interactions of the Mechanosensory Proteins Wsc2 and Wsc3 for Stress Resistance in Saccharomyces cerevisiae. Issue 9 (1st September 2020) - Vélez-Segarra, Vladimir; González-Crespo, Sahily; Santiago-Cartagena, Ednalise; Vázquez-Quiñones, Luis E; Martínez-Matías, Nelson; Otero, Yamirelis; Zayas, Julián J; Siaca, Rafael; del Rosario, Jeanmadi; Mejías, Inoushka; Aponte, José J; Collazo, Noelani C; et al.
Abstract: Antifungal drug discovery and design is very challenging because of the considerable similarities in genetic features and metabolic pathways between fungi and humans. However, cell wall composition represents a notable point of divergence. Therefore, a research strategy was designed to improve our understanding of the mechanisms for maintaining fungal cell wall integrity, and to identify potential targets for new drugs that modulate the underlying protein-protein interactions in Saccharomyces cerevisiae . This study defines roles for Wsc2p and Wsc3p and their interacting protein partners in the cell wall integrity signaling and cell survival mechanisms that respond to treatments with fluconazole and hydrogen peroxide. By combined genetic and biochemical approaches, we report the discovery of 12 novel protein interactors of Wsc2p and Wsc3p . Of these, Wsc2p interacting partners Gtt1p and Yck2p, have opposing roles in the resistance and sensitivity to fluconazole treatments respectively. The interaction of Wsc2p with Ras2p was confirmed by iMYTH and IP-MS approaches and is shown to play a dominant role in response to oxidative stress induced by hydrogen peroxide. Consistent with an earlier study, Ras2p was also identified as an interacting partner of Wsc1p and Mid2p cell wall integrity signaling proteins. Collectively, this study expands the interaction networks of the mechanosensory proteins of the Cell Wall Integrity pathway.